Poverty and social exclusion: An alternative spatial explanation - Krzysztofik, Robert; Dymitrow, Mirek; Grzelak-Kostulska, Elżbieta; Biegańska, Jadwiga (Bulletin of Geography. Socio-economic Series, 2017)
Poverty and social deprivation remain some of the biggest concerns in the face of obtaining social sustainability. In this respect, the continuing immense spatial differences between individual localities of seemingly similar characteristics have puzzled social scientists for decades. In quest for a better understanding, this article highlights the role of spatial heterogeneity as a factor conducive to the formation of functionally derelict areas, which in turn play a crucial role in the formation of spatial mismatch. Using two case studies from Poland, one from a big city and one from a small village, we explore the relationality between the phenomena of spatial heterogeneity, functional dereliction and spatial mismatch, whose mutual reinforcement seems to lead to a specific kind of deprivation in terms of scale and intensity. Special attention is paid to the role of spatial heterogeneity, which under certain conditions is capable of changing from being a developmental stimulant to becoming a destimulant. We argue that taking greater account of the intricate historical contexts responsible for the resistance of some pressing socio-economic problems is key to breaking the deadlock in the implementation of ineffective sustainability policies .